Website-Based Electronic Voting (E-Voting) System in the Bem Unwaha General Election - Rizky Imam Mukti; Primaadi Airlangga (NEWTON: Networking and Information Technology, 2025)
The election of the Student Executive Board (BEM) of KH.A Wahab Hasbullah University (UNWAHA) has undergone a transformation from a conventional system to a website-based e-voting system. This research aims to implement and start the e-voting system used in the UNWAHA BEM election. The method used in this research is Research and Development (R&D) with the stages of needs analysis, system design, implementation and evaluation. Data was collected through surveys of e-voting system users to measure ease of access, satisfaction, security, attractiveness and problems encountered.